The Relationship between Trans-Lesional Conduction, Motor Neuron Pool Excitability, and Motor Function in Dogs with Incomplete Recovery from Severe Spinal Cord Injury - Lewis, Melissa J. (J Neurotrauma, 2017)
Spontaneous, acute, complete thoracolumbar spinal cord injury (TL-SCI) in dogs frequently results in permanent deficits modeling chronic paralysis in people. Recovery of walking without recovery of sensation has been interpreted in dogs as reflexive spinal walking. To evaluate this assumption, this study characterized the electrophysiological status of motor and sensory long tracts and local reflex circuitry in dogs with absent recovery of sensation after acute TL-SCI and correlated findings to gait scores. Twenty dogs with permanent deficits after acute, clinically complete TL-SCI and 6 normal dogs were prospectively enrolled. Transcranial magnetic motor evoked potentials (MEPs), somatosensory evoked potentials (SSEPs), H-reflex, and F-waves were evaluated. Gait was quantified using an ordinal, open field scale (OFS) and treadmill-based stepping and coordination scores (SS, RI). MEP latency and H-reflex variables were compared between cases and controls. Associations between presence of MEPs, SSEPs, F-waves or H-reflex variables, and gait scores were determined. Pelvic limb MEPs were detected in 4 cases; no case had trans-lesional sensory conduction. Latency was longer and conduction velocity slower in cases than controls (p(a) = 0.0064, 0.0023, respectively). Three of 4 cases with pelvic limb MEPs were ambulatory, and gait scores (OFS, SS, RI) were each associated with presence of trans-lesional conduction (p(a) = 0.006, 0.006, 0.003, respectively). H threshold in cases (mean, 3.2mA ±2.5) was lower than controls (mean, 7.9mA ±3.1; p(a) = 0.011) and was inversely associated with treadmill-based scores, SS, and RI (p(a) = 0.042, 0.043, respectively). The association between pelvic limb MEPs and gait scores supports the importance of descending influence on regaining walking after severe TL-SCI in dogs rather than just activation of spinal walking. The inverse association between H-reflex threshold and gait scores implies that increases in motor neuron pool excitability might also contribute to motor recovery.